Politinio žiniasklaidos diskurso apibrėžtys: žiniasklaidos, kaip politinės komunikacijos dėmens, tyrimas Renata Matkevičienė - Matkevičienė, Renata (Information & Media, 2008)
Žiniasklaidos dalyvavimas šiandieniame politiniame gyvenime akivaizdus ir nekvestionuojamas. Pastaraisiais metais ji tapo bene aktyviausia politinės komunikacijos veikėja, taip pat aktyviai politikos srities dalyvių panaudojama terpe siekiant tikslų. Šio straipsnio tikslas – apibrėžti ir nusakyti politinio žiniasklaidos diskurso teorinio tyrimo dėmenis. Išsikėlus tikslą, siekiama nustatyti politinio žiniasklaidos diskurso apibrėžties ir tyrimo apibrėžtumą, ištirti žiniasklaidos, kaip politinio proceso veikėjos, vaidmenis ir tyrimo galimybes. Šiame straipsnyje teigiama, kad politiniame žiniasklaidos diskurse atsiskleidžia dvejopas žiniasklaidos, kaip politinės komunikacijos elemento, vaidmuo: pirmiausia politinio žiniasklaidos diskurso analizė nurodo žiniasklaidą kaip vietą (erdvę), kurioje vyksta sąveika tarp politikos veikėjų, visuomenės ir žiniasklaidos institucijų; antra, žiniasklaida gali būti tiriama kaip institucija, formuojanti politinį diskursą, arba priemonė, taikoma jam formuoti. Determination of political mass media discourse: investigation of mass media as an element for political communication Renata Matkevičienė Summary Participation of the mass media in nowadays political life is very actually and not questioned process. In recent years mass media became one of the most active participants in political communication, and as well it became an instrument for other participants of political sphere to influence electorate, and other audiences. The aim of the article is to define and to determine elements of theoretical investigation of political mass media discourse. The idea of the article is to find out frames from determination and theoretical investigation of mass mediated political discourse, to research mass media as the active participant of political processes, to clear up its roles and possibilities for research. In this article there is made a supposition that in political mass mediated discourse there could be seen double role of the mass media as the element of political communication. From one side political mass mediated discourse analysis presents mass media as the sphere (place) where the interaction between poli tical actors, society and mass media institutions take place. On the other hand mass media could be used as an institution that sets political discourse or as an instrument that could be used to form it. Hedonistic and consumer society puts its impact on political mass mediated discourse. Contemporary mass mediated political discourse presents not discussions on political items and ideologies, but outputs of packaged politics (for example, political actors are presented not as participants of political sphere, but as show stars, with highlighted their human characteristics. As a conclusion there could be stated that investigation of political mass mediated discourse is possible in only one way – when there are investigated all discourses that influence political mass mediated discourse, such as: political discourse, mass media discourse, public discourse. Interrelations between those discourses could not be affected by one discourse and that could be seen especially during political election campaign.